1999
DOI: 10.1177/002221949903200508
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Prevention of Dyslexia

Abstract: This study examined the effects of training in phonological awareness on kindergarten children. Comparisons of children at risk (i.e., children with initially low levels of metalinguistic ability) with initially average and advanced children revealed that training gains were similar for all of these groups. Furthermore, training had comparable long-term effects on reading and spelling in Grades 1 and 2 for each group. In fact, the trained children at risk showed better reading and spelling performance than a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…It is possible that the applied trainings would be more effective if used in a group of less experienced readers at the very beginning of formal literacy instruction. This applies to the phonological awareness intervention in particular, as especially phonological awareness interventions were shown to be of use in preschool children 14 , 27 . However, this is not the case of the AVG training, as the previously tested children were roughly at the same age (mean age around 10 years) 19 , 20 as the participants of the current study (mean age 11.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the applied trainings would be more effective if used in a group of less experienced readers at the very beginning of formal literacy instruction. This applies to the phonological awareness intervention in particular, as especially phonological awareness interventions were shown to be of use in preschool children 14 , 27 . However, this is not the case of the AVG training, as the previously tested children were roughly at the same age (mean age around 10 years) 19 , 20 as the participants of the current study (mean age 11.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we were unable to compare the effects of small group instruction to the effects of 1:1 instruction in the synthesis. It is notable that the three studies with the largest group sizes also had the lowest effects among the studies implementing group instruction (Foorman, Francis, Beeler, Winikates, & Fletcher, 1997;O'Connor, Notari-Syverson, & Vadasy, 1996;Schneider, Roth, & Ennemoser, 2000). It does appear that smaller group size does increase the intensity of the intervention.…”
Section: Duration Of Interventionmentioning
confidence: 98%
“…In a review of extensive reading interventions that met high-quality research criteria, Scammaca et al (2007) identified four studies that focused on kindergarten children with identified early reading risk (Gunn, Biglan, Smolkowski, & Ary, 2000;Lennon & Slesinski, 1999;Schneider, Roth, & Ennemoser, 2000;Torgesen, Wagner, Rashotte, Rose, et al, 1999) and shared considerable commonality in the focus of intervention. All included at least one experimental condition that focused on explicit phonemic and code-based instruction.…”
Section: P R I O R R E S E a R C H O N S U P P L E M E N T A L R E A D I N G I N T E R V E N T I O N Smentioning
confidence: 99%